Efficacy and safety of avatrombopag in combination with immunosuppressive therapy in treatment-naïve and relapsed/refractory severe aplastic anaemia: protocol for the DIAAMOND-Ava-FIRST and DIAAMOND-Ava-NEXT Bayesian Optimal Phase II trials - Stephane Heritier; Alisa Higgins; Piers Blombery; Robin Filshie; Paul Lacaze; Kate Wilson; William Stevenson; Lauren Young; Zoe McQuilten; Jennifer Curnow; Lucy Fox; Vanessa Fox; et al. (BMJ Open)
Introduction Immunosuppressive therapy (IST) with antithymocyte globulin (ATG) and ciclosporin is standard of care for patients with severe aplastic anaemia (sAA) not eligible or suitable for allogeneic stem cell transplant. While patients respond to IST, few achieve complete responses and a significant proportion are refractory or relapse. The addition of eltrombopag, a thrombopoietin-receptor agonist (TPO-A), to IST has been shown to improve haematological responses in sAA. Avatrombopag is a second-generation TPO-A with potential advantages over eltrombopag. However, to date avatrombopag has not been studied in sAA.Methods and analysis Investigator-initiated, single-arm registry-based Bayesian Optimal Phase II trial of avatrombopag conducted in two cohorts, patients with untreated sAA (FIRST cohort) and in patients with sAA that has relapsed or is refractory to IST (NEXT cohort). In the FIRST cohort, participants receive IST (equine ATG and ciclosporin) plus avatrombopag from day 1 until day 180 at 60 mg oral daily, with dose adjusted according to platelet count. Participants in the NEXT cohort receive avatrombopag at 60 mg oral daily from day 1 until day 180, with or without additional IST at the discretion of the treating clinician.For each cohort, two primary endpoints (haematological response and acquired clonal evolution) are jointly monitored and the trial reviewed at each interim analysis where a ‘go/no-go’ decision is made by evaluating the posterior probability of the events of interests.Ethics and dissemination The trial has received ethics approval (Monash Health RES-18-0000707A). The trial conduct will comply with ICH-GCP and all applicable regulatory requirements. The results of the trial will be submitted to a peer-review journal for publication.Trial registration number ACTRN12619001042134, ACTRN12619001043123.